PROCEDURES FOR PRODUCING, ADOPTING, CHANGING AND REVOKING TECHNICAL REGULATIONS - Ismatova Ozoda Normatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: Technological regulations - this many enterprises in the work required that documents the most important categories of the one to be can. That's in addition the product of the production of or all of any activity out increasing the process of characterizing knew how to act and the rules collection. Technical regulations directly to the organization of the main activities of the procedures and stages, see out, the product work out for at all possible is and necessary requirements provides a description of, as well as, the obtained goods to the final description of his own into gets.